On-Surface Synthesis Proceedings of the International Workshop On-Surface Synthesis, École des Houches, Les Houches 25-30 May 2014 - Gourdon, André (Advances in Atom and Single Molecule Machines, 2016)
With contributions by leading international experts, this book presents a detailed compilation of a new and very active field. It is the first book devoted to the covalent coupling of molecular precursors on surfaces that allows the preparation of 0D, 1D and 2D molecules that cannot be synthesized in solution. This book is aimed at students and researchers interested in nanochemistry and molecular devices and it gives the reader a pedagogical up-to-date vision of the most recent developments. The editor ensures a multidisciplinary approach involving molecular chemistry, surface sciences, surface spectroscopies, theory, scanning tunneling and non-contact atomic force microscopies.